Vacuolar processing enzyme (VvβVPE) from Vitis vinifera, processes seed proteins during ovule development, and accelerates seed germination in VvβVPE heterologously over-expressed Arabidopsis. (September 2018) - Gong, Peijie; Li, Yan; Tang, Yujin; Wei, Rong; Huijun, Zhu; Wang, Yuejin; Zhang, Chaohong
Highlights: 1st time to report VPE genes' function in grapevine. 1st paper to show ovule protein band polymorphism on SDS-PAGE in whole ovule developing stage of grapevine. VvβVPE expression pattern was revealed within seeded/seedless grapes by boht mRNA and protein level. VPE enzyme activity was increased while VvβVPE was heterologous overexpressed in Arabidopsis . Various forms of VvβVPE are essential for vitis ovule maturation and its function also involved in seed germination. Abstract: Vacuolar processing enzymes (VPEs), belonging to cysteine protease, are responsible for processing seed protein during maturation. Stenospermocarpic grapes occur self-abortion in fertilized embryos during the ovule development, which affects the formation of matured seed proteins. However, little is known about VPE functions in ovule self-defeating. Here, we investigated the role of one seed-type VPE gene, VvβVPE . Sequence analysis showed that all ORFs (Open reading frames) of VvβVPE from 19 seed/seedless genotypes are highly conserved. At the transcriptional level, VvβVPE was specifically expressed during ovule development, with distinct expression patterns: it increased gradually in seeded grapes; while weakly expressed in seedless grapes. Whereas, at the translational level, 3 forms of VvβVPE were expressed during ovule development in seeded grape: precursor βVPE (pβVPE), intermediate βVPE (iβVPE) and finally, active mature βVPE (mβVPE). By contrast, in seedless grape, VvβVPE only exists as pβVPE at whole developmental stage of ovule. for confirming these expression patterns, 12 seeded/seedless genotypes were sampled and analyzed. Furthermore, VPE enzyme activity was increased in Arabidopsis overexpressing VvβVPE, leading to faster germination. Our study indicated that VvβVPE is essential for grapevine ovule maturation through various forms and is involved in seed germination.